Extragalactic jets from every angle : proceedings of the 313th Symposium of the International Astronomical Union held in Puerto Ayora, Galapagos Islands, Ecuador, September 15-19, 2014 - International Astronomical Union. Symposium 2014 : Puerto Ayora, Ecuador); Massaro, Francesco; Cheung, Chi C.; Lopez, Ericson D.; Siemiginowska, Aneta (2015)
"Extragalactic jets provide the direct observational evidence for a connection between supermassive black holes and their surrounding cosmic environments. They deliver the energy released by an accreting black hole across large distances and impact the formation and evolution of surrounding structures, carrying information about the black hole's power, spin, accretion state and characteristic timescales. IAU Symposium 313 brings together observational astronomers working across the electromagnetic spectrum with theorists, to investigate our understanding of the physics of relativistic jets. They address questions on topics such as: unification scenarios for blazars and radio galaxies, the interactions between jets and their environments, jet composition and structure, the role of magnetic fields, mechanisms of particle acceleration, high-energy emissions, and the scaling of physical jet phenomena with black-hole mass, from extragalactic to galactic sources. This volume benefits observers and theorists, both researchers and advanced students, working on relativistic jets in distant galaxies."--
[1] Multi-frequency observations of highly variable relativistic jets -- [2] Jet structure, collimation, and the role of the magnetic field -- [3] Particle acceleration mechanisms, cosmic rays, and high-energy radiative processes -- [4] Black hole -- extragalactic jet connections: statistics, intermittency, unification -- [5] Jet interactions and their role in the structural evolution and feedback -- [6] Cosmological evolution of jet progenitors -- [7] Close to the black hole: launching jets -- [8] Extragalactic and galactic jet synergies.
Includes bibliographical references and index.
Keywords: Astrophysical jets -- Congresses; Congressen (vorm)